The Stability of Magnetic Levitation Milling System Based on Modal Decoupling Control - Xiaoli Qiao; Xiaoping Tang (Shock and Vibration)
Milling stability not only reduces the surface quality of the workpiece but also seriously restricts the high-speed development of CNC machine tools. The electric spindle rotor system with the active magnetic bearing has a strong gyro coupling effect, and with the increasing rotor speed, it will become a major unfavorable factor for the stability of the system during high-speed milling. The strong gyro coupling effect makes the stability region narrow at the time of high-speed milling. So, a modal decoupling control method that can reduce the effects of the gyro effect on the magnetic levitation milling system under high-speed milling is proposed. The effects of the gyro coupling of the magnetic bearing rotor on the milling stability region before and after the decoupling control are studied, which show that the modal decoupling control technology can reduce the effects of the gyro effect on the magnetic levitation milling system.